Analysis of Dynamics Characteristic of Multi-span Cracked Rotor-rolling Bearing - Shen Qian; Xie Weisong; Liu Jiahang; He Zhenpeng (Jixie chuandong)
Based on the additional stiffness caused by the crack,the non-linear Hertz contact of the rolling bearing,and the Varying compliance（ VC） vibration caused by the variation of the bearing stiffness of the rolling bearing,a double-span rotor model with transverse crack under rolling bearing support is established by Lagrange equation. Considering the problems of eccentricity and rubbing,the nonlinear dynamics behaviors of the system caused by singular and coupled faults are numerically simulated by the variable step Runge-Kutta method. The effects of crack propagation,crack angle and rolling bearing radial clearance on the system response are analyzed based on the bifurcation diagram,axial locus diagram,Poincare section diagram and 3 D spectrum. The results show that when a single fault occurs,a large range of chaotic motions occur in the supercritical rotational speed region. When the coupling fault occurs,the response of the system is affected by the combination of unbalanced rotation and VC vibration in the subcritical rotational speed region and enters the quasi-periodic,the frequency division begins after exceeding the critical speed,it shows strong nonlinear characteristic. When the crack is shallow,the influence on the system response is not obvious. When the crack is deeper,the response of the system changes obviously in the high revolving speed area. The crack angle has a great influence on the chaos motion. There is no essential effect on the periodic movement,the system response is sensitive to the change of the rolling bearing clearance. The research results have certain guiding significance for controlling and predicting the failure of rotating machinery.